Pengenalan BIPA melalui Materi, Strategi dan Teknik dalam Pengajaran di Kabupaten Aceh Barat, Provinsi Aceh - Jamaluddin Nasution; Firman Parlindungan (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2022)
Introduction to Indonesian Language for Foreign Speakers (ILFS) through materials, strategies and techniques in teaching is a Community Service Activities (CSA) which was aimed to provide training and introduction to ILFS in West Aceh District, Aceh Province. This activity was carried out on 23 to 25 May, 2022 with the theme “Technical Guidance and Introduction the Basics of ILFS Teaching for Lecturers, Teacher Candidates, and ILFS Activists”. For the theme “Materials, Strategies and Techniques in Teaching ILFS” delivered by Jamaluddin Nasution was held on 24 May 2022 from 08.00 A.M. – 5.00 P.M. The ILFS teaching materials provided were: 1) opening class; 2) compiling syllabus and lesson plans; 3) culture and tourism in teaching ILFS; 4) choosing the appropriate material; and 5) game materials in teaching. This Community Service Activity was also carried out by donating a book from the author entitled “Culture Shock in Uzbekistan” to the Language Center of Teuku Umar University West Aceh Regency. In this case, ILFS teaching can be used as a medium and a means of linguistic diplomacy to introduce Indonesia to foreign countries. Therefore, ILFS needs introducing to the community, especially lecturers, teachers and ILFS activists. This activity aimed to encourage them to actively participate in teaching ILFS both at domestic and abroad. Thus, ILFS can be used as a medium and a means of diplomacy that helps the Indonesian government to introduce Indonesian language and culture to the international world.